RETRACTION NOTICE TO “Challenges in Hyflex Learning in Zambales, Philippines” - Mobo, Froilan D.; Garcia, Ana Liza R.; Talosig, Jackson C (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
This article entitled “Challenges in Hyflex Learning in Zambales, Philippines” (2022), authored by Froilan D. Mobo, Ana Liza R. Garcia, and Jackson C. Talosig, published in Vol. 3, No. 10 of International Journal of Multidisciplinary: Applied Business and Education Research. 3(10), 2150 – 2153 has been retracted as requested by the authors.